Journal of Applied Volcanology Society and Volcanoes - Hudson-Doyle, Emma E.; Lindsay, Jan Marie; Leonard, Graham; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: BioMed Central.)
Journal of Applied Volcanology is an international journal with a focus on applied research relating to volcanism and particularly its societal impacts. Characterising volcanic impacts and associated risk relies on not only quantifying physical threat but also understanding social and physical vulnerability and resilience. The broad aim of volcanologists in this domain is to increase public resilience to volcanic risk via research that reduces both human fatalities and volcanic impacts on livelihoods, infrastructure, and the economy. Journal of Applied Volcanology fills an important gap for scientists who want to publish research that addresses this aim and wish to reach a broad audience. The journal has a holistic view of the relationship between volcanoes and society, and therefore welcomes intra- cross- multi- inter- and transdisciplinary articles that deal with volcanoes and society. Research topics covered by the journal include: the impacts of eruptions on communities; methods for risk analysis; risk management; community preparedness, response to and recovery from volcanic hazard events; health issues related to volcanism; social adaptation to volcanic hazards; policy and institutional aspects of volcanic risk management; applications of physical volcanology, geophysics and remote sensing to volcanic crisis mitigation. The journal aims for rapid publication of high-impact research and review papers.
Keywords: Natural disasters; Geophysics; Physical geography; Technology$1 (BSociological aspects.s; Natural Hazards; Geophysics; Earth System Sciences; Science, Technology and Society